TINJAUAN HUKUM ISLAM TERHADAP TRANSAKSI GO-FOOD : Studi Pada Restoran Ayam Gepuk Pak Gembus Kunciran Pakujaya Tangerang Selatan - Rijal Sasmita; Irvan Iswandi; Ali Aminullah (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Islamic Engagement Law is part of Islamic Law in the field of muamalah which manages human behavior in running their economy relationship. In this digital era, many business actor utilizes online transportation. One of online transportations is Go-Jek which in it there is Go-Food facility which ease the customers to order food via online. The problem context in this research was how the implementation of Go-Food eas at Gepuk Chicken Restaurant of Mr. Gembus Kunciran Pakujaya, driver and consumers, and how was the Islamic law review on the implementation of this transaction. This research was included into field research that was conducted at Gepuk Chicken Restaurant of Mr. Gembus, driver of Go-jek and Go-food, and consumers. To obtain valid data, primary and secondary data were employed. The data collection methods were interview, observation, and documentation. After the data were collected, then they were analyzed by using qualitative method with thinking method inductively. Based on the research result, the customer ordered the food using Go-food application, then total price appears, the price appears is more expensive compared to when the customer buy the food by themselves at the restaurant because of the price registered by the restaurant at Go food has been taxed 20% from the real price, then Go-food party will seek the nearest driver, the driver will confirm the order to the customer and buy the food ordered by the customer, then the driver pays for the food then deliver it to the customer’s location, the customer pays the order with the cost fee of the driver which is determined by Go-food party in accordance with the distance. The implementation of this Go-food transaction is concluded into ijarah agreement between the driver and customer, while the commerce agreement occurs between the customer and the restaurant party. Both agreements can be categorized into wakalah bil ujrah agreement. The driver represented the customer to buy the food and obtain fee for it. About the tax imposed for the food price in Go-food is the evidence of promotion service rent that must given by the restaurant to Go-food party. This has fulfilled the pillar and requirements of commerce in order to be hindered from gharar and riba element and also strongly suitable with the syara’ regulation namely clear quality and quantity of the goods until it is enough with the order, therefore it is allowed in Islamic law.